The Effect of Audio Distraction Technique Hearing The Murrotal Al-Qur’an on Anxiety in Pre-Operative Patients at Muhammadiyah Gresik Hospital - Purnomo, Didik Andika; Sari, Diah Jerita Eka; Widiyawati, Wiwik; Widiharti, Widiharti (Kontribusia : Research Dissemination for Community Development, 2024)
Anxiety in pre-cesarean section patients can be due to fear of pain or death. One form of nurse intervention in reducing anxiety is by giving audio distractions namely diverting attention to other stimuli by listening to the audio of the Qur’an Murottal. The purpose of this study was to determine the patient’s level of anxiety before and after audio distraction listening to The Qur’an Murottal. The study design used is Pre-Experiment one-group pre-test-post test design. The entire population studied patients who will face the first operation cesarean section and elective at the Hospital Muhammadiyah Gresik with a number of 41 patients. The number of samples that met the inclusion criteria as many as 37 patients. Collecting data anxiety level using the APAIS questionnaire before and after giving audio distraction techniques. Analysis using statistical tests Wilxocon Signed Rank Test with significance level α <0.05. The result showed most of respondents experiencing severe anxiety 51.4% before doing audio distraction listening to the Qur’an Murottal, there was a decrease in anxiety after audio distraction listening to the Qur’an murottal was as much as 54.1% are not worried. From the analysis of the statistical test obtained value α = 0.001 which means that α <0,05 then Ho is rejected and H1 is accepted, which means that there is an effect of audio distraction listening to the Qur’an murottal on the anxiety of preoperative cesarean section patients.